2010
DOI: 10.1080/00986445.2010.493118
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Inhibition and Adsorption Behavior of Malachite Green Dye on Aluminum Corrosion

Abstract: Malachite green dye (MG) was studied as a corrosion inhibitor for aluminum in 1.0 mol dm À3 HCl and 0.5 mol dm À3 KOH using the gravimetric technique. The results revealed an inhibiting effect of MG, which was highly restrained in 0.5 M KOH and pronounced in 1.0 M HCl. MG inhibited the corrosion reaction in the acidic medium by adsorption on the metal=solution interface following the FloryHuggins isotherm. Inhibition efficiency increased with MG concentration and synergistically increased in the presence of io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…The major driving force of quantum chemical research is to understand and explain the functions of ethyl hydroxyethyl cellulose in molecular forms. Among quantum chemical methods for evaluation of corrosion inhibitors, density functional theory (DFT) has shown significant promise [21][22][23] and appears to be adequate for pointing out the changes in electronic structure responsible for inhibitory action. The geometry of the inhibitor is in ground state, as well as the nature of their molecular orbitals, HOMO (the highest occupied molecular orbital) and LUMO (the lowest unoccupied molecular orbital), that are involved in the properties of activity of inhibitors [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…The major driving force of quantum chemical research is to understand and explain the functions of ethyl hydroxyethyl cellulose in molecular forms. Among quantum chemical methods for evaluation of corrosion inhibitors, density functional theory (DFT) has shown significant promise [21][22][23] and appears to be adequate for pointing out the changes in electronic structure responsible for inhibitory action. The geometry of the inhibitor is in ground state, as well as the nature of their molecular orbitals, HOMO (the highest occupied molecular orbital) and LUMO (the lowest unoccupied molecular orbital), that are involved in the properties of activity of inhibitors [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Oguzie et al 109 reported that Malachite green dye, especially at high concentrations, is an effective corrosion inhibitor for AA1060 aluminium alloy (98.8% aluminium) in aerated 1 M HCl solution at 30-60 °C, using the WL technique. The inhibition effectiveness increased with increasing Malachite green dye concentration, but decreased with increasing temperature.…”
Section: Organic Corrosion Inhibitors In Hcl Solutionmentioning
confidence: 99%
“…amounts of the inhibitor have been utilized to demonstrate the best isotherm to locate the adsorption behavior. The adsorption isotherms of Frumkin [1], Temkin [18], Flory-Huggin [7], Langmuir [19], and Freundlich [20] were fitted to . The correlation coefficient 2 was utilized to compare all these models to choose the best isotherm.…”
Section: Adsorption Isothermmentioning
confidence: 99%
“…Most of the acid inhibitors are organic materials with N, S, and O atoms and various bonds in their structure. In addition, many N-heterocyclic compounds have been reported as effective inhibitors for metals corrosion and alloys in aqueous media [2][3][4][5][6][7]. The absorption of inhibitors on metal surfaces leads to coverage of active sites of metal surface and thereby leads to a decrease in the metal corrosion rate.…”
Section: Introductionmentioning
confidence: 99%